Aligning Chatbot Features with Industry Needs: A Comparative Study of User Expectations in Utilitarian and Hedonic Sectors for SMEs - Bespalko, Denys; van Hamond, Jason; Neggers, Margot; Kokkinou, Alinda (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This study explores the optimal chatbot orientation—socially oriented (SO) or task-oriented (TO)—for small and medium-sized enterprises (SMEs) in hedonic versus utilitarian industries. Through a mixed-methods approach combining quantitative data from 166 participants and qualitative interviews, it examines user preferences for chatbot interaction styles, focusing on perceived ease of use (PEOU) and usage intention (UI). Findings highlight a strong preference for SO chatbots in hedonic contexts, emphasizing engaging, human-like interactions, while utilitarian industries showed no significant preference, with efficiency taking precedence. Correlation analysis revealed a robust link between perceived ease of use and usage intention for SO chatbots, underscoring their potential to enhance user engagement. The research provides actionable insights for SMEs to tailor chatbot designs to industry-specific customer expectations, aligning digital tools with business goals and customer satisfaction.